Optimal control of an industrial-scale evaporation process: Sodium aluminate solution - Chai, Q.; Yang, C.; Teo, Kok Lay; Gui, W. (Pergamon, 2012)
A mathematical model of the evaporation system in the form of a state space model with multiple time delays is constructed. On this basis, an optimal control of an industrial-scale alumina evaporation process is obtained, where the objective is to find a control such that the specific quality of the sodium aluminate solution control is met with the least energy usage and the constraints on the state and the control are satisfied. Then, a numerical algorithm is developed for solving this optimal control problem. It is applied to study the optimal control of a practical alumina evaporation process and the results obtained are highly satisfactory.